AS POSSIBILIDADES E OS ENTRAVES POLÍTICO-NORMATIVOS PARA A SUPERAÇÃO DO ESTADO DE COISAS INCONSTITUCIONAL CARACTERIZADOR DA SITUAÇÃO DA POPULAÇÃO CARCERÁRIA BRASILEIRA DE TRANSEXUAIS E TRAVESTIS - AMARAL NETO, João Francisco (2024)
The general objective of the master's thesis in question is to evaluate the public policy applied to the Brazilian prison population of transsexual and transvestite people by virtue of normative acts originating mainly from the National Council of Justice (CNJ), such as CNJ Resolution nº 348/2020, with a view to identifying its potential to overcome the Unconstitutional State of Affairs characterized by the situation. It also has specific objectives to investigate the status quo of the Brazilian prison population of transsexuals and transvestites and the originating antecedents of the main normative acts analyzed; Identify the subjects who participated in the elaboration of these regulations, determining the participation of their target audience, as a political subject; and discusses the constitutional and human rights principles provided for in international treaties that were covered by such normative acts. The research modality adopted was, albeit timidly, the political evaluation of public policies. And, to support this methodological procedure, Pierre Bourdieu's theoretical framework is developed.